Pneumothorax in a Neonate after Foreign Body Ingestion - Patil, Pashant Sadashiv; Kothari, Paras; Gupta, Abhaya; Kekre, Geeta; dikshit, Vishesh; kamble, Ravi; Mudkhedkar, Kedar (Journal of Neonatal Surgery, 2016)
Please see Fulltext